Дослідження та аналіз процессів взаємодії сервісів в мікро-сервісній архітектурі - Белименко, В. С. (ХНУРЕ, 2024)
In the digital era, microservices architecture emerges as a key for developing scalable, flexible, and reliable systems. It allows for the independent updating and deployment of system components, enhancing development efficiency and system resilience. A primary challenge in microservices architecture is service interaction, encompassing effective communication, dependency management, data consistency, and transaction pattern implementation. Overcoming these challenges requires understanding service interaction nuances, including network communication and resilience strategies.
Keywords: мікро-сервісна архітектура